Kidney Function Is Not Related to Brain Amyloid Burden on PET Imaging in The 90+ Study Cohort - Lau, Wei Ling; Fisher, Mark; Fletcher, Evan; DeCarli, Charles; Troutt, Hayden; Corrada, María M.; Kawas, Claudia; Paganini-Hill, Annlia (Frontiers in Medicine, 2021)
Cognitive decline is common in chronic kidney disease (CKD). While the evidence of vascular cognitive impairment in this population is robust, the role of Alzheimer’s pathology is unknown. We evaluated serum cystatin C-estimated glomerular filtration rate (eGFR), brain amyloid-β positron emission tomography (PET) imaging, and cognitive function in 166 participants from The 90+ Study. Mean age was 93 years (range 90 to 107) and 101 (61%) were women; 107 participants had normal cognitive status while 59 participants had cognitive impairment no dementia (CIND) or dementia. Mean + standard deviation cystatin C was 1.59 + 0.54 mg/L with eGFR 40.7 + 18.7 mL/min/1.73m2. Higher amyloid-β burden was associated with dementia, but not with age, diabetes, hypertension or cardiovascular disease. We found no association between brain amyloid-β burden and cystatin C eGFR. We previously reported that kidney function was associated with cognition and cerebral microbleeds in the same cohort of oldest-old adults (90+ years old). Collectively, these findings suggest that microvascular rather than Alzheimer’s pathology drives CKD-associated cognitive dysfunction in this population.